La diversidad: el reto de la educación inclusiva - Martínez Ocaña, Bertha E. (2017)
In this article we review the concepts of diversity, inclusion, educational inclusion, highlighting diversity as a value that enriches us. It presents the national and international agreements that promote inclusive education, as a right to education for All.